PENILAIAN MUTU RUMAH SAKIT TUGU IBU DENGAN THE MALCOLM BALDRIGE NATIONAL QUALITY AWARD TAHUN 2005 = QUALITY ASSESSMENT OF TUGU IBU HOSPITAL USING THE MALCOLM BALDRIGE NATIONAL ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Background: Currently, hospitals face increased competitions, hence, maintaining high quality standard becomes increasingly vital. The patients are the quality indicators and a committed strong leader is needed for quality improvement. For the past three years, Tugu Ibu Hospital has a decline in the quality services offered. This is the result of a poor quality management. The objective of the research is to study the quality of Tugu Ibu Hospital using MBNQA. Methods: A descriptive research was done with 20 interviews. Data were gathered using in depth interview, document investigation, and observation. The interview was based on 7 criteria in MBNQA, which are leadership, strategic planning, focus on patients, other costumers and market, measurement, analysis and management knowledge, staff focus, process management and organizational performance results. Result: The hospitalâs quality is relatively poor. Criteria with the highest scores were criteria 4 measurement, analysis and management knowledge. The other criteria are relatively low. The quality of this hospital scored at 251,25 out of 1000 points. This is describes that Tugu Ibu Hospital in the beginning to answer basic requirement for seven criteria. Altough a big gap happened in approach and deployment in the several categories. Conclusion: We are advice to build a strong leadership team, involved senior leadership to develop and deploy of strategic planning. We also suggest to created value costumer and implement MBNQA criteria. Keywords: quality, hospital, malcolm baldrige